Social Media Marketing, Brand Loyalty, and Entrepreneurial Growth: A Path toward Sustainable Business Advantage - Putra, Pandi; Dinsar, Arfandy; Normazi, Nurul Najwa Binti; Ilahi, Andi Alfianto Anugrah; Faturahman, Fahmi (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2024)
This study examines how social media marketing influences business sustainability through the mediating role of brand loyalty among micro, small, and medium enterprises in the trade sector. Academically, it advances marketing and entrepreneurship theory by integrating the Resource-Based View, Customer-Based Brand Equity, and Triple Bottom Line frameworks to explain how digital capabilities transform into sustainable competitive advantage. Using data from 200 respondents analyzed with Partial Least Squares–Structural Equation Modeling, the findings confirm that effective social media engagement enhances customer loyalty, which in turn drives sustainable business performance. The study reveals that digital marketing success is rooted in trust-based relationships rather than short-term promotion, emphasizing that relational value mediates technological advantage. These insights provide practical implications for MSME owners and policymakers to strengthen digital literacy, relational marketing, and sustainability-oriented strategies to ensure long-term business resilience in the evolving digital economy.